Stochastic stability analysis of periodic uncertain markov jump systems with partially known information - Zhu, L.; Yin, YanYan; Liu, Y.; Liu, F. (ICIC International, 2017)
© 2017 ISSN 1881-803X. In this paper, the issue of stochastic stability and stabilization of periodic Markov jump systems with uncertain transition probabilities and parameters is investigated. The partially unknown transition probability matrix is described as a polytope with uncertain vertices. By constructing a Lyapunov function, sufficient conditions are established under which the system is stochastically stable. Numerical example is given to show the effectiveness of the method proposed.